The Relationship Between Work-Related Stress and Depression: A Scoping Review - Jean-Baptist du Prel; Adrijana Koscec Bjelajac; Zrinka Franić; Lorena Henftling; Hana Brborović; Eva Schernhammer; Damien M. McElvenny; Damien M. McElvenny; Eda Merisalu; Nurka Pranjic; Irina Guseva Canu; Lode Godderis; et al. (Frontiers Media S.A., 2024)
ObjectivesWork-related stress is highly prevalent. Recent systematic reviews concluded on a significant association between common work-related stress measures and depression. Our scoping review aims to explore whether work-related psychosocial stress is generally associated with depression or depressiveness, the extent and methodology of the primary research undertaken on this topic and to elucidate inconsistencies or gaps in knowledge.MethodsWe searched for literature in Pubmed, PsycInfo and Web of Science including full reports in seven languages published between 1999 and 2022 and applied the PRISMA statement for scoping reviews criteria.ResultsOf 463 primarily identified articles, 125 were retained after abstract and full-text screening. The majority report significant associations between work-related stress and depression. Cross-sectional studies are most prevalent. Sufficient evidence exists only for job strain and effort-reward imbalance. Most studies are from Asia, North America and Europe. The health sector is the most studied. Several research gaps such as the lack of interventional studies were identified.ConclusionThe consistency of most studies on the significant association between work-related stress and depression is remarkable. More studies are needed to improve evidence and to close research gaps.